Evaluating trauma severity scores: Predicting mortality in patients with geriatric trauma - Elnaz Vafadar Moradi; Sayyed Majid Sadrzadeh; Hosein Zakeri; Behrang Rezvani; Mahdi Azari; Ghazaleh Ghorbannezhad (Hong Kong Journal of Emergency Medicine)
Abstract Background Trauma in older adults poses distinct challenges due to age‐related physiology changes, increased comorbidities, and diminished physiological reserves. Identifying predictive factors of mortality is crucial for forecasting outcomes in this vulnerable population. This study aims to compare the effectiveness of the Trauma Injury Severity Score (TRISS) and the New Injury Severity Score (NISS) in predicting mortality among patients with geriatric trauma. Materials and Method This cross‐sectional study was conducted at a Level‐1 academic trauma center. We evaluated all patients presenting with trauma, enrolling those aged 65 and older. Data were collected from the trauma registry of Department of Emergency Medicine in Mashhad, Iran between April 2021 and February 2022, and TRISS and NISS scores were computed using an electronic database. Statistical analyses, including descriptive and inferential statistics, were performed using SPSS version 26. Results A total of 393 patients were analyzed; 211 (53.7%) were men and 182 (46.3%) were women, with a mean age of 75.16 ± 7.58 years. The overall mortality rate was 3.5% (14 patients). Notably, the Glasgow Coma Scale score, oxygen saturation, and systolic blood pressure on admission were significantly lower in patients who did not survive. The optimal cutoff points for predicting mortality were identified as 2.5 for NISS and 98 for TRISS, yielding sensitivities of 92% and 96%, and specificities of 26% and 25%, respectively. The areas under the receiver operating characteristic curve for NISS and TRISS were 0.748 and 0.743, respectively. Conclusion Although both the NISS and TRISS scores demonstrated comparable efficacy in predicting mortality among patients with geriatric trauma, TRISS exhibited slightly better predictive accuracy and high sensitivity. Surviving patients had lower NISS and higher TRISS scores, indicating differentiation in outcomes based on these metrics. These findings suggest that both scoring systems may be useful tools in assessing mortality risk in this population.